2021
DOI: 10.3390/ijms22147531
|View full text |Cite
|
Sign up to set email alerts
|

Cera Flava Alleviates Atopic Dermatitis by Activating Skin Barrier Function via Immune Regulation

Abstract: Cera Flava (CF), a natural extract obtained from beehives, is widely used in dermatological products owing to its wound healing, wrinkle reduction, UV-protective, and skin cell turnover stimulation effects. However, its effect on AD-like skin lesions is unknown. In this study, we used a mouse model of AD to evaluate the effects of CP at the molecular and phenotypic levels. Topical house dust mite (HDM) sensitization and challenge were performed on the dorsal skin of NC/Nga mice to induce AD-like cutaneous lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…However, abnormal activation of TLR2 may lead to activation of T helper cell-related immune responses and production of keratinocyte-specific CKs and ChKs, which trigger allergic immune responses in the chronic phase of AD [ 69 ]. Therefore, strategies that finely modulate TLR2 expression or function promise to restore barrier function and immune balance in AD [ 64 , 65 , 70 ]. Thus, TIRAP is an essential player in the development of inflammation, which could be successively reduced by stimulation with osthole in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, abnormal activation of TLR2 may lead to activation of T helper cell-related immune responses and production of keratinocyte-specific CKs and ChKs, which trigger allergic immune responses in the chronic phase of AD [ 69 ]. Therefore, strategies that finely modulate TLR2 expression or function promise to restore barrier function and immune balance in AD [ 64 , 65 , 70 ]. Thus, TIRAP is an essential player in the development of inflammation, which could be successively reduced by stimulation with osthole in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the experiment, the same experimenter raised all animals in the same location at the same time. The sample size was determined from a similar experiment reported in the literature ( 40 , 41 ). Prior to the study, a protocol was prepared without registration.…”
Section: Methodsmentioning
confidence: 99%
“…Therapies for AD have focused on restoring the skin barrier through increased skin moisture retention. A study by Park et al (2021) examined the effects of cera flava (CF), which is a natural extract from beehives that is modified through heath compression filtration and purification, on a mouse model of AD. 15 Using house dust mite as an irritant, the authors found that use of CF attenuated symptoms of pruritus and increased skin moisture content; restored skin barrier proteins like filaggrin, claudin-1, and occludin; and downregulated immune signaling associated with an inflammatory response.…”
Section: Uses In Dermatitis and Psoriasismentioning
confidence: 99%